2015
DOI: 10.1080/2162402x.2015.1040215
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of TNF-α signaling benefits cancer therapy by suppressing effector regulatory T cell expansion

Abstract: Effector but not naive regulatory T cells (Treg cells) can accumulate in the peripheral blood as well as the tumor microenvironment, expand during tumor progression and be one of the main suppressors for antitumor immunity. However, the underlying mechanisms for effector Treg cell expansion in tumor are still unknown. We demonstrate that effector Treg cell-mediated suppression of antitumor CD8C T cells is tumor-nonspecific. Furthermore, TNFR2 expression is increased in these Treg cells by Affymetrix chip analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
0
42
0
1
Order By: Relevance
“…We found that GRP78 high HCC tissues recruited more CD68 + macrophages in the stroma, and in vitro studies demonstrated that Exo‐TMs polarized macrophages to the M2 phenotype. Moreover, there are evidences suggesting that cancer cells promote macrophage production of inflammatory mediators, such as IL‐6 and TNF‐α, to facilitate tumor metastasis . Here, we found that Exo‐TMs not only increased macrophage IL‐6 and TNF‐α expression but also up‐regulated protumor factor IL‐10 expression, suggesting that ER‐stressed HCC cells may “educate” macrophages toward TAMs to facilitate disease progression.…”
Section: Discussionmentioning
confidence: 54%
“…We found that GRP78 high HCC tissues recruited more CD68 + macrophages in the stroma, and in vitro studies demonstrated that Exo‐TMs polarized macrophages to the M2 phenotype. Moreover, there are evidences suggesting that cancer cells promote macrophage production of inflammatory mediators, such as IL‐6 and TNF‐α, to facilitate tumor metastasis . Here, we found that Exo‐TMs not only increased macrophage IL‐6 and TNF‐α expression but also up‐regulated protumor factor IL‐10 expression, suggesting that ER‐stressed HCC cells may “educate” macrophages toward TAMs to facilitate disease progression.…”
Section: Discussionmentioning
confidence: 54%
“…Tumor Necrosis Factor Alpha (TNF-α) activates the transcription factor NFκB, thus promoting proliferation and metastasis of tumor cells [44,46]. Several studies have demonstrated the link between increased TNF mRNA levels in the tumor tissue and advanced stages of CRC [47][48][49], suggesting that targeting TNF-α can be applied in treatment of CRC, especially when it has progressed from ulcerative colitis [50,51]. However, some authors report suppression of this cytokine in tumor, attributed to promoter-methylation of the gene [52].…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells can accumulate in both the peripheral blood and the cancer microenvironment and have been shown to expand during cancer progression suggesting that Treg cells may play a pivotal role in suppressing anti-tumor immunity. 100 In support of this hypothesis, Treg cell depletion or functional suppression results in augmented T-cell immune responses against cancer in both mice and humans. 101 As an additional link between B7-H4 and Treg cells, a study using human cervical carcinoma found that B7-H4 promoted the growth of Treg cells.…”
Section: Functional Connection Between B7-h4 and Tregsmentioning
confidence: 99%